Epidemiology and diversity of Plasmodium species in Franceville and their implications for malaria control - Larson Boundenga; Yann Vital Sima-Biyang; Neil Michel Longo-Pendy; Michelle Bignoumba; Clark Mbou-Boutambe; Clauve Jauvert Moukagni-Mussadji; Dorothé Marielle Wora; Fabrice Kassa-Kassa; Richard Onanga; Cyrille Bisseye; Francine Ntoumi; Ayola Akim Adegnika; et al. (Scientific Reports)
Abstract Malaria is a significant public health challenge in Gabon, with high prevalence rates in rural and semi-urban areas. This study investigated Plasmodium infection prevalence among outpatients at a medical laboratory in Franceville, Gabon, in 2020. Data from 500 patients were analyzed, revealing an overall infection rate of 33.2% and the presence of four Plasmodium species: P. falciparum, P. malariae, P. ovale, and possibly P. vivax for the first time in Gabon. Co-infections were common, with P. falciparum and P. ovale spp. being the most prevalent at 23.5%. Asymptomatic infections accounted for 81.3% of cases, while symptomatic infections were 18.7%. P. falciparum was associated with symptomatic cases, while non-falciparum species were linked to asymptomatic infections. The findings suggest Franceville has perennial malaria transmission, highlighting the role of Plasmodium species diversity in disease severity and clinical presentation, including the first report of P. vivax infection in the Gabonese population.